Essays on the adoption and welfare effects of conservation management practices in the U.S. - Thomas, Raymond Joseph (Kansas State University, 2024)
Analyzing the Use and Intensity of Carbon Farming Practices in the U.S. The implementation of carbon farming management strategies is an area of ongoing research. Practices such as partial tillage or complete no-till, cover crop production, crop rotation, and land use change (LUC), aid in sequestering carbon from the atmosphere in the soil. These practices can also benefit producers by preserving water quality, soil productivity, and improving resilience to changing climate conditions. Research suggests that maximizing the sequestration potential of these practices requires the joint adoption and use of multiple complementary practices. Though U.S. producers have begun implementing some carbon practices, others face barriers to entry that make joint use difficult. Thus, there is a need to understand the factors that influence the adoption and use of multiple sustainable farming practices. This study seeks insight into the current landscape of joint carbon practice management decisions by U.S. producers. Using a Multinomial Logit Model (MNL) the likelihood of joint use of four conservation practices: (1) no/reduced tillage, (2) land use change (LUC), (3) cover crops, and (4) crop rotation is evaluated while controlling demographic factors, farm characteristics, weather, climate, and soil/field conditions. The data for this research comes from the United States Department of Agriculture (USDA) Agricultural Resource Management Survey (ARMS) conducted by the Economic Research Service (ERS). Supplemental data includes gSSURGO soil data from the USDA Natural Resource Conservation Service and climate/weather data from the PRISM Climate Group database. The results identify a significant relationship between the likelihood of using complementary practices and control variables. The weather, climate, and soil variable groups greatly influenced jointly used practices. Implications from these results can aid policymakers in crafting incentives to encourage and support the implementation of sustainable production practices. Evaluating the Welfare Implications of Carbon Farming Practices in the U.S. Carbon farming conservation practices, such as reduced-tillage, no-till, land conversion, crop rotation, and cover crops, are critical in ongoing efforts to reduce climate change impacts. However, these practices can require additional inputs from producers, potentially impacting the financial stability of farm operations. Studies argue that producers may benefit financially from carbon farming practices through potential increases in yield and crop quality resulting from improved environmental soil health conditions. However, maximizing the mitigation benefits may require the use of more than one carbon farming practice. Thus, there is a need to understand how carbon farming practices impact the financial well-being of agricultural producers. Further insight into this area can assist policymakers and private sector entities in further developing and improving mechanisms to encourage the use of these practices. The purpose of this study is to gain insight into the welfare implications of carbon farming practice implementation for producers. The analysis uses a propensity score matching approach to evaluate the financial impact of using one or more carbon farming practices on agricultural operations in the U.S. This research uses data from the USDA’s Agricultural Resource Management Survey (ARMS) which provides information on the management practices, input use, and economic well-being of U.S. producers. The results from the analysis suggest that the use of a single carbon farming practice has either a negative or insignificant impact on net farm income when compared to farms that use none. However, the use of multiple practices is shown to have a significantly positive impact on net farm income compared to farm operations that use only one. Assessing the Impact of Policy Reform on Conservation Management Behaviors in the U.S. Government policies can be a mechanism to influence the management decisions of agriculture producers in the U.S. in ongoing efforts to mitigate climate change. Through implementing programs and offering financial incentives for using carbon farming practices, farmers in the U.S. may be encouraged to increase the use of these practices and reallocate greater amounts of land toward conservation efforts. The Farm Bill is a key piece of government legislation designed to help ensure the longevity and stability of agricultural production in the U.S. Previous versions sought to address natural resource-related challenges in the nation through the development of programs such as the Conservation Reserve Program (CRP) and the Environmental Quality Incentive Program (EQIP). The programs still receive updates with new revisions of the bill. As policies continue to be developed and revised, research is needed to assess whether these programs have significantly impacted the conservation management decisions of farmers in the U.S. The purpose of this research is to assess the impact of the 2014 USDA Farm Bill on the conservation behavior of U.S. agriculture producers. The analysis uses a fixed effects model to examine the impact of the revised Farm Bill legislation on conservation behavior using a pseudo-panel approach to identify the impact across time. This research uses data from the USDA’s Agricultural Resource Management Survey (ARMS) which provides information on the management practices, input use, and economic well-being of U.S. producers. The results show that after the 2014 revisions, the average amount of conservation practices implemented by farms significantly increased along with the amount of land allocated to conservation activities.
Keywords: Conservation; Carbon farming; Adoption; Welfare; Policy